STRATEGI PEMERINTAH DAERAH KABUPATEN SIAK DALAM PENANGGULANGAN BENCANA BANJIR DI KECAMATAN SUNGAI MANDAU TAHUN 2013 - Mariana, Rina; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The unitary Republic of Indonesia is responsible to protect all the people of Indonesia and the country of Indonesia with the aim to provide protection to the lives and livelihoods, including the protection of the disaster, Siak Regency is a regency in Riau Province where several sub-district is on the edge outskirts Siak River , which allows the occurrence of disasters, floods and forest fires, floods that hit most of the sub-district in Siak, one of them in the study of floods that occurred at Sungai Mandau District in 2013. The purpose of this study was to determine how the strategy undertaken by the Regional Government of Siak (Regional Disaster Management Agency, Social Services, Public Health Service) in flood disaster management at Sungai Mandau District 2013. While the method used is qualitative research method, wherein the method This indicates to the research procedures that produce descriptive data that phrase or note made in the form of interviews and documentation were then taken to a conclusion. Based on the research results, the strategy undertaken by the Regional Government of Siak (Regional Disaster Management Agency, Social Services, and the Department of Health) is by way of cooperation, coordination, and communication. Then in this case there is one factor inhibiting the strategy can work well, among them the lack of planning, lack of facilities or transportation, lack of public awareness so that strategies do not yet well established. Siak government in disaster management, which occurred at Sungai Mandau District has not run well in this case because of the Government of Siak not perform the functions of coordination and management of the government as well.Keywords: Cooperation, Coordination, Communication.